2004
DOI: 10.1074/jbc.m312675200
|View full text |Cite
|
Sign up to set email alerts
|

Folding of Active Calcium Channel β1b -Subunit by Size-exclusion Chromatography and Its Role on Channel Function

Abstract: Voltage-gated calcium channels mediate the influx of Ca 2؉ ions into eukaryotic cells in response to membrane depolarization. They are hetero-multimer membrane proteins formed by at least three subunits, the poreforming ␣ 1 -subunit and the auxiliary ␤-and ␣ 2 ␦-subunits. The ␤-subunit is essential for channel performance because it regulates two distinct features of voltage-gated calcium channels, the surface expression and the channel activity. Four ␤-subunit genes have been cloned, ␤ 1-4 , with molecular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…However, the G max was more affected than the plasma membrane expression of Ca V 2.2 (81 and 62% reduction, respectively, when coexpressed with Ca V ␤1b). The reason for this is likely to be that Ca V ␤ not only traffics the channel to the surface but also increases the maximum open probability of the channel, as suggested previously (Wakamori et al, 1999;Meir et al, 2000;Neely et al, 2004).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, the G max was more affected than the plasma membrane expression of Ca V 2.2 (81 and 62% reduction, respectively, when coexpressed with Ca V ␤1b). The reason for this is likely to be that Ca V ␤ not only traffics the channel to the surface but also increases the maximum open probability of the channel, as suggested previously (Wakamori et al, 1999;Meir et al, 2000;Neely et al, 2004).…”
Section: Discussionmentioning
confidence: 71%
“…However, the mechanism for this increase remains controversial, being attributed to increased trafficking (Bichet et al, 2000), increased maximum open probability (Neely et al, 2004), or both. Our data agree with previous studies showing biochemically that the amount of Ca V 1.2 channels in the plasma membrane was increased by Ca V ␤ subunits (Altier et al, 2002;Cohen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The ␤ subunit has been proposed to both enhance the functional expression and influence the biophysical properties of the Cav1 and Cav2 channels. Whereas some studies have described that ␤ subunit hyperpolarizes the voltage dependence of activation, augments the maximal open probability, and consequently results in increased current through individual channel and macroscopic current density (3,10,30,31), others observed that the ␤ subunit either promotes the insertion of Cav channels into the plasma membrane, as determined by gating charge measurements, imaging, and biochemical methods (7,(32)(33)(34)(35)(36)(37) or has no effect on membrane insertion at all (38). The mechanism of the Cav ␤ subunit effect on surface expression has generally been attributed to masking an ER retention signal in the ␣1 subunits (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Since Ca V β modulates both chimeras in a canonical fashion, our results are still consistent with the view that Ca V β increases channel activity through a coil-to-helix transition of this region. 26,40 However, the sequence content as well as the secondary structure of the I-II linker appears to be determinants of the efficiency in the coupling between voltage sensor and channel opening.…”
Section: Discussionmentioning
confidence: 99%
“…All capped cRNA were synthesized and Xenopus laevis oocytes were prepared, injected and maintained as previously reported. 40 Electrophysiological recordings were performed at 22°C with the cut-open oocyte technique four to six days after cRNA injection as described. 31 The internal recording solution contained 120 mM n-methylglucamine, 10 EGTA mM and 10 mM HEPES, pH 7.0 and the external solution contained 10 mM Ba 2+ , 96 mM n-methylglucamine and 10 mM HEPES, pH 7.0.…”
Section: Discussionmentioning
confidence: 99%